Gender Variation in Squatting Facet of Talus Bone (Bangladesh Journal of Anatomy, 2024)
Context: Talus is the most important key bone of the tarsals as it carries the weight in static and kinetic position during movement. Squatting facet is present on the superior surface of the neck of the talus. Appearance of squatting facet occur due to postural adaptation like squatting position during extreme dorsiflexion in climbing, prolonged standing, harvesting, performing prayers and high arched foot. Squatting facet can determine the race of an individual, can be utilized by forensic experts and anthropologists while dealing with unidentified bones. Material and Method: This cross sectional observational study was conducted on 150 fully ossified dry adult human left tali (of which 83 were male and 67 were female). Types of squatting facets were observed in the Department of Anatomy of Dhaka Medical College, Dhaka from January, 2018 to December,2018. Results: In male, out of 83 left tali, lateral squatting facet were observed in 24 cases (28.9%), medial squatting facet in 4 cases (4.8%), combined (medial and lateral) squatting facet in 9 cases (10.8%), no squatting facet in 46 cases (55.4%). In female, out of 67 left tali, lateral facet were found in 15 cases (22.4%), medial facet in 2 cases (3.0%), combined facet in 5 cases (7.5%) and no squatting facet in 45 cases (67.2%). Conclusion: In the present study, lateral squatting facets were the commonest in both male and female.Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 1, pp. 13-16